Interaction between magnesium and methylglyoxal in diabetic polyneuropathy and neuronal models - Strom, Alexander; Strassburger, Klaus; Schmuck, Martin; Shevalye, Hanna; Davidson, Eric; Zivehe, Fariba; Bönhof, Gidon; Reimer, Rudolph; Belgardt, Bengt-Frederik; Fleming, Thomas; Biermann, Barbara; Burkart, Volker; et al. (Molecular metabolism, 2021)
Objective - The lack of effective treatments against diabetic sensorimotor polyneuropathy demands the search for new strategies to combat or prevent the condition. Because reduced magnesium and increased methylglyoxal levels have been implicated in the development of both type 2 diabetes and neuropathic pain, we aimed to assess the putative interplay of both molecules with diabetic sensorimotor polyneuropathy. - Methods - In a cross-sectional study, serum magnesium and plasma methylglyoxal levels were measured in recently diagnosed type 2 diabetes patients with (n = 51) and without (n = 184) diabetic sensorimotor polyneuropathy from the German Diabetes Study baseline cohort. Peripheral nerve function was assessed using nerve conduction velocity and quantitative sensory testing. Human neuroblastoma cells (SH-SY5Y) and mouse dorsal root ganglia cells were used to characterize the neurotoxic effect of methylglyoxal and/or neuroprotective effect of magnesium. - Results - Here, we demonstrate that serum magnesium concentration was reduced in recently diagnosed type 2 diabetes patients with diabetic sensorimotor polyneuropathy and inversely associated with plasma methylglyoxal concentration. Magnesium, methylglyoxal, and, importantly, their interaction were strongly interrelated with methylglyoxal-dependent nerve dysfunction and were predictive of changes in nerve function. Magnesium supplementation prevented methylglyoxal neurotoxicity in differentiated SH-SY5Y neuron-like cells due to reduction of intracellular methylglyoxal formation, while supplementation with the divalent cations zinc and manganese had no effect on methylglyoxal neurotoxicity. Furthermore, the downregulation of mitochondrial activity in mouse dorsal root ganglia cells and consequently the enrichment of triosephosphates, the primary source of methylglyoxal, resulted in neurite degeneration, which was completely prevented through magnesium supplementation. - Conclusions - These multifaceted findings reveal a novel putative pathophysiological pathway of hypomagnesemia-induced carbonyl stress leading to neuronal damage and merit further investigations not only for diabetic sensorimotor polyneuropathy but also other neurodegenerative diseases associated with magnesium deficiency and impaired energy metabolism.
Gesehen am 23.04.2022